Ulk1, Not Ulk2, Is Required for Exercise Training-Induced Improvement of Insulin Response in Skeletal Muscle - Drake, Joshua C.; Wilson, Rebecca J.; Cui, Di; Guan, Yuntian; Kundu, Mondira; Zhang, Mei; Yan, Zhen (Frontiers in Physiology, 2021)
Unc51 like autophagy activating kinase 1 (Ulk1), the primary autophagy regulator, has been linked to metabolic adaptation in skeletal muscle to exercise training. Here we compared the roles of Ulk1 and homologous Ulk2 in skeletal muscle insulin action following exercise training to gain more mechanistic insights. Inducible, skeletal muscle-specific Ulk1 knock-out (Ulk1-iMKO) mice and global Ulk2 knock-out (Ulk2-/-) mice were subjected to voluntary wheel running for 6 weeks followed by assessment of exercise capacity, glucose tolerance, and insulin signaling in skeletal muscle after a bolus injection of insulin. Both Ulk1-iMKO and Ulk2-/- mice had improved endurance exercise capacity post-exercise. Ulk1-iMKO did not improve glucose clearance during glucose tolerance test, while Ulk2-/- had only marginal improvement. However, exercise training-induced improvement of insulin action in skeletal muscle, indicated by Akt-S473 phosphorylation, was only impaired in Ulk1-iMKO. These data suggest that Ulk1, but not Ulk2, is required for exercise training-induced improvement of insulin action in skeletal muscle, implicating crosstalk between catabolic and anabolic signaling as integral to metabolic adaptation to energetic stress.